2014
DOI: 10.1590/rou.2014.036
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia related to HIV infection /AIDS: a critical review

Abstract: ResumoIntrodução: A presença de manifestações bucais em indivíduos HIV positivos é bastante comum, sendo que a xerostomia aparece como um dos problemas mais frequentes, podendo levar a uma redução na qualidade de vida dessa população. Objetivo: Este estudo objetivou realizar uma revisão crítica sobre a relação entre xerostomia e a infecção pelo HIV, a fim de despertar a atenção do cirurgião-dentista quanto à importância da atenção odontológica dirigida a esses pacientes. Material e método: Foram incluídos arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In our study, CD4 count did not show impact on salivary gland function, similar to results reported by Lopez, et al and Pavithra, et al [2,9]. This is contrary to studies done by Navesh, et al and Tinos, et al where low CD4 count was reported as risk factor for salivary gland hypofunction [10,11]. The conflicting results could be due to our identifying participants being seen at a clinical site who were in care and had already recovered their CD4 counts by being on cART.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, CD4 count did not show impact on salivary gland function, similar to results reported by Lopez, et al and Pavithra, et al [2,9]. This is contrary to studies done by Navesh, et al and Tinos, et al where low CD4 count was reported as risk factor for salivary gland hypofunction [10,11]. The conflicting results could be due to our identifying participants being seen at a clinical site who were in care and had already recovered their CD4 counts by being on cART.…”
Section: Discussionsupporting
confidence: 82%